-4x - 2(8x + 1) = -(-2x - 10)
The first step is to distribute. On the left side of the equation, multiply the -2 by both terms inside the parentheses; on the right side of the equation, multiply the -1 by both terms inside the parentheses:
-4x - 2(8x + 1) = -(-2x - 10)
-4x - 16x - 2 = 2x + 10
Next, combine like terms.
-4x - 16x - 2 = 2x + 10
-20x - 2 = 2x + 10
Then subtract 2x from both sides and add 2 to both sides to get like terms together; combine like terms.
-20x - 2 = 2x + 10
-20x - 2x = 2 + 10
-22x = 12
Lastly, divide both sides by -22 and simplify.
-22x = 12
x = 12/-22
x = -6/11
Answer:
-6/11